A new Helluodes Westwood species from Western Ghats with notes on habitat, distribution and phylogenetic relationships of genera Helluodes Westwood and Physocrotaphus Parry of the tribe Physocrotaphini Chaudoir (Insecta: Coleoptera: Carabidae: Anthiinae) - Sabu, Thomas K.; Abhitha, Prabhakar; Zhao, Danyang (Zootaxa, 2008)
Description of Helluodes devagiriensis, n.sp. from western slopes of the Western Ghats, a global biodiversity hot spot in southwest India, is provided along with redescriptions of all species of Helluodes Westwood and Physocrotaphus Parry (H. taprobanae Westwood, H. westwoodi Chaudoir, Physocrotaphus ceylonicus Parry), keys to the genera of tribe Physocrotaphini and the species of genus Helluodes, notes on a curious sexually dimorphic character of species in the tribe and on termitophilous and geophilous habits of genus Helluodes, a discussion of the geographic distribution and phylogenetic relationships of the genera, and supportive evidence for the divergence of Physocrotaphini Chaudoir from Zuphiini Bonelli. Based on distributional patterns and phylogenetic relationships, (1) origin of the tribe in the southwest region of the Greater Indian Plate is hypothesized with Helluodes as basal stock; (2) Helluodes is endemic to the Western GhatsSri Lanka global hot spot of biodiversity; (3) Physocrotaphus is endemic to the globally outstanding montane evergreen forest ecoregion of Sri Lanka; (4) Pogonoglossus Chaudoir is a derivative of the Helluodes ancestral stock that dispersed into southeast Asia and beyond before Deccan trap formation; and (5) Physocrotaphus is a later derivative of the Helluodes stock after the separation of Sri Lanka from the Indian mainland.